EVALUATION OF ACCOUNTABILITY AND TRANSPARENCY MANAGEMENT OF VILLAGE FUND ALLOCATIONS - Audrey Pramesti Pallawarukka; Muhammad Ansar; Haryono pasang kamase (Adpebi Science Series, 2024)
The purpose of this study is to explore the evaluation of the accountability of existing village fund allocation management and formulate the most possible accountability improvement. This study uses a case study strategy, namely qualitative data analysis of the results of interviews and direct observation. Informants involved in this study include village heads, village secretaries, and maranatha village communities. The results showed accountability and transparency of village fund allocation management in maranatha village, sigi sub-district, sigi city, has been running well. Transparency the management of ADD in maranatha village runs transparently this can be seen from the existence of information that is easily accessible by the community and the existence of good communication between village officials and the community so that the management of ADD is considered transparent.